ANALYSIS OF BUSINESS FEASIBILITY IN EKSPANSION ABILITY PT. MEKARSARI WARNA PERKASA - Dea Gita Permatasari; Reswanda Reswanda (STKIP Singkawang, 2021)
In the world of the plastic industry, currently it is experiencing a fairly rapid development. In its efforts to develop the company carries out investment activities. PT. Mekarsari Warna Perkasa is one of the business actors engaged in plastic dye trading which will expand by building a color matching laboratory. This type of research is qualitative descriptive using investment criteria analysis techniques to see whether the project is feasible or not. The results showed that the NPV value was Rp. 165,168,085.69, NET B / C of 1.26, IRR value of 19.86%, then the payback period for 3 years 7 months and BEP of 85.49%, namely the turnover of Rp. 1,231,094,004. So it can be concluded overall that this expansion plan is feasible to run with a cash flow that is always positive using the assumption of sales of 1,440,000,000 per year, with 100% of own capital, and a discount factor of 10%. The benefits of this research for business owners in carrying out expansion plans are expected to use 100% of their own capital so that there are no additional bank loan interest costs, and it is hoped that future researchers will become a reference for analysis using the external capital component.